Managing partners of people diagnosed with Chlamydia trachomatis: a comparison of two partner testing methods. Issue 5 (22nd October 2003) - Østergaard, L; Andersen, B; Møller, J K; Olesen, F; Worm, A-M
Abstract : Objective: To compare the effectiveness of "home sampling" with that of "office sampling" for testing partners to men and women infected with Chlamydia trachomatis . Method: A randomised controlled effectiveness trial took place in the general community in Denmark. 1300 index women and 526 index men (⩾18 years) with a positive test result for C trachomatis were identified. Of these, 414 index women and 148 index men gave implied consent. Index patients were randomly assigned to provide their partner(s) through the past 12 months with either (1) a kit by which partner(s) could be tested by home sampling, or (2) a kit by which partner(s) could only be tested by seeing a healthcare professional (office sampling). The mainoutcome measure was the proportion of index patients who had at least one partner tested for C trachomatis . Results: The proportion of index women with at least one partner tested was higher in the home sampling group (0.26) than in the office group (0.12) (difference 0.14; 95% CI 0.10 to 0.19; p<0.0001) and so it was for index men (0.15 v 0.03; difference 0.12; 95% CI 0.07 to 0.16; p<0.0001). Also the proportion of index women for whom at least one partner was identified as infected was higher in the home sampling group compared with the office group (0.11 v 0.07, p=0.01). The corresponding figures for index men were 0.06 v 0.01, p=0.02. Conclusion: The effectiveness of partner testing is higher when partners of C trachomatis infected patients are offered home sampling than when they are offered office sampling.